Ketidaksetujuan terhadap Dispensasi Perkawinan di Bawah Umur ditinjau dari Aspek Hukum dan Moral - Greace Br Sembiring, Ivana; Arthur Jonathan, Yeremia; Hafizhah, Annisa (PT. Meja Ilmiah Publikasi, 2025)
Marriage law has undergone changes, especially in regulating the minimum age. Before the changes, the law set the minimum marriage age for men at 19 years and the marriage age for women at 16 years. In the amendment of Law Number 1 of 1974 to Law Number 16 of 2019 concerning Marriage, the minimum age for marriage for both men and women is 19 years. In the process, although the minimum age for marriage has increased, currently there are still many marriages of underage children, both legally and not. This is because the marriage dispensation granted by the court is still in force with several strong reasons and evidence submitted by the applicant to the judge so that it can convince the judge to grant a decree. The type of research used is normative with normative juridical research methods. The approach used in this research is a statutory approach (Statute Approach) using secondary data which becomes primary legal material. The results of the research will show the results of the analysis of legal and moral aspects related to disapproval of the underage marriage dispensation and its role in reducing the number of legally illegal early marriages.